2018
DOI: 10.1016/j.jfda.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable, fruit, and phytonutrient consumption patterns in Taiwan

Abstract: Phytonutrients may play important roles in human health and yet only recently a few studies have described phytonutrient consumption patterns, using data obtained from daily consumption methods. We aimed to estimate the phytonutrient content in Taiwanese diets and analyzed main food sources of 10 major phytonutrients. In this study, food items and dietary data gathered with the 24-hour dietary recall from 2908 participants in the 2005-2008 Nutrition and Health Survey in Taiwan were used to create a food phyton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
(38 reference statements)
0
12
2
1
Order By: Relevance
“…Beside the expected difference in the consumption of fruit and whole grain cereals between women and men, our study unexpectedly showed no such gender difference for vegetables, which is in contrast with previous studies ( 35 , 36 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Beside the expected difference in the consumption of fruit and whole grain cereals between women and men, our study unexpectedly showed no such gender difference for vegetables, which is in contrast with previous studies ( 35 , 36 ).…”
Section: Discussioncontrasting
confidence: 99%
“…This fourth highest occurrence of β-cryptoxanthin in plasma is unique, since it occurs in a limited number of foods that are not dietary staples. Mandarin oranges, papaya, sweet potato leaf, watermelon, and related products are the key contributor of β-cryptoxanthin in the human diet [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the subjects in this current study met the recommended guidelines for fruit and vegetable intake. In Taiwanese adults, 20% had the recommended number of servings for fruit and 30% met the Taiwan Food-Guide recommendations for vegetables [27]. Studies show that fruits and vegetables contain a large number of vitamins, minerals, and dietary fiber, and insufficient intake of fruits and vegetables is associated with a higher risk of CRC [28,29].…”
Section: Discussionmentioning
confidence: 99%